Yield of cupuaçu fruits in response to liming and potassium fertilization in agroforestry systems in the Western Amazon - Ayres, Marta Iria da Costa; Alfaia, Sonia Sena (Pesquisa Agropecuaria Brasileira, 2007)
The effect of liming and potassium fertilization on cupuaçu fruit production was evaluated in agroforestry systems (AFS), where cupuaçu was one of the main components. The experiment was conducted on soils classified as Inceptsol. The randomized blocks design was used with three replicates, in a 2x3 factorial scheme, where the factors were two liming levels (0 and 3 t ha-1 of lime) and three doses of potassium (0, 40 and 80 kg ha-1 K2O). During four successive years, cupuaçu yield was evaluated regarding the number and weight of the fruits. The treatments without lime K fertilization had a positive and linear effect on fruit production, showing that cupuaçu plants have a K deficiency on those soils. With liming fruit yield levelled at 80 kg ha-1 K2O showed a tendency toward stability, suggesting that liming improves the efficiency of K fertilization.